Instrumen Diagnostik dalam Pembelajaran Fisika: Tinjauan Literatur Sistematis berbasis Scopus Menggunakan Kerangka PRISMA (2010-2025) - Gilang Ramadhan; Supahar; Heru Kuswanto (Universitas Negeri Semarang, 2025)
Research on diagnostic instruments in physics education has grown significantly in recent years; however, a comprehensive mapping of research trends, methodological characteristics, and research gaps based on international databases is still limited. Therefore, this study aims to analyze the development and application of diagnostic instruments in physics education in the range of 2010 to 2025 using publications indexed by Scopus. A total of 36 articles that met the criteria were analyzed following the PRISMA framework to identify trends, methodological characteristics, and research gaps. The findings show that four-tier diagnostic tests dominate this field (50%), followed by three-tier instruments (22%), reflecting a shift toward more comprehensive assessments that evaluate students’ answers, reasoning, and confidence levels simultaneously. Research topics mostly focus on mechanics, heat, and electricity, while modern physics and advanced concepts are still rarely explored. Most studies used analysis based on Classical Test Theory (91.6%) for validation, with limited adoption of Rasch modeling and Item Response Theory. Study participants were dominated by college students (50%) and high school students (44%), who showed minimal attention to vocational students and active teachers. Furthermore, paper-based formats still dominate despite increasing interest in digital and adaptive assessments. In conclusion, these findings provide a comprehensive overview of research trends in diagnostic instruments within physics education and highlight several research gaps that may inform the development of technology-based diagnostic assessments and the adoption of modern psychometric approaches in future studies.